Effects of a 12-Week Skipping Exercise Program on Leg Endurance in Competitive Badminton Players: A Randomized Controlled Trial - Ririn Irena; Ardila Melati; Vlad Adrian Geanta; ⁠Ayu Mayzura Simbolon; Retha Foret (Inspiree)
The  purpose  of  the study. Leg endurance is vital for badminton, yet training methods for its enhancement are inadequately explored. This study examined the impact of a skipping exercise regimen on leg endurance and performance metrics among competitive badminton athletes.